Clinical‐radiological, histological and genetic analyses in a lung transplant recipient with Mounier–Kuhn syndrome and end‐stage chronic obstructive pulmonary disease. (21st May 2014) - Mitterbauer, Andreas; Hoetzenecker, Konrad; Birner, Peter; Mildner, Michael; Prosch, Helmut; Streubel, Berthold; Taghavi, Shahrokh; Klepetko, Walter; Ankersmit, Hendrik Jan
Abstract Background and Aims The Mounier–Kuhn syndrome (MKS) is a rare disease characterized by a pathological dilation of the trachea and the bronchial system. The etiology of the disorder remains elusive, but genetic alterations and degradation of elastic fibers are thought to be involved in the pathogenesis. No causative treatment is available although transplantation is an option for end‐stage disease. Here, we describe a patient suffering from MKS who received a double lung transplant at our department. Methods Since a familial clustering of MKS is discussed in the literature, we performed a chromosomal analysis and an array‐comparative genomic hybridization (CGH) to search for genetic abnormalities. At the time of transplantation, we collected samples from the bronchi and performed hematoxylin and eosin (HE), Elastic von‐Gieson (EVG) and immunohistochemical stains of the explanted MKS bronchus, a control bronchus and of the inflammatory infiltrates. Specimens of main bronchi from the donor lung harvested for transplant served as control. Bronchial smears were taken from both main bronchi of the recipient for microbiological cultures. Results No genetic alterations could be found in chromosomal analysis and in array‐CGH. Histological analysis revealed a strong reduction of elastic fibers in the submucosal connective tissue and a diffuse inflammatory infiltrate, mainly comprised of CD4+ cells. In addition, immunohistochemistry showed increased matrix metalloproteinases (MMPs) protein expression of MMP‐1, 2, 3 and 9. Conclusions Based on our findings, we hypothesize that MKS is a chronic inflammatory disease characterized by an MMP‐mediated degradation of submucosal elastic fibers.